2016
DOI: 10.3765/amp.v3i0.3666
|View full text |Cite
|
Sign up to set email alerts
|

Sonority-Driven Stress does not Exist

Abstract: This paper presents new acoustic evidence against sonority-driven stress in Gujarati. Gujarati has been the subject of more stress descriptions than any other sonority-driven stress case, and is one of the very few where stress is reported to be sensitive to multiple sonority levels. However, all these impressionistic descriptions of Gujarati stress disagree with each other in significant ways. In contrast, this paper presents the results of a production experiment. Acoustic measurements show that [a] does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The experiments reported here found modest acoustic evidence in favor of fixed initial stress, failed to find clear acoustic correlates of sonority-driven stress as described by de Lacy (2002;, and found that speakers have inconsistent stress intuitions. These results are in keeping with other recent literature on Gujarati (Shih 2016;2018).…”
Section: Discussionsupporting
confidence: 93%
“…The experiments reported here found modest acoustic evidence in favor of fixed initial stress, failed to find clear acoustic correlates of sonority-driven stress as described by de Lacy (2002;, and found that speakers have inconsistent stress intuitions. These results are in keeping with other recent literature on Gujarati (Shih 2016;2018).…”
Section: Discussionsupporting
confidence: 93%
“…We conclude that Slovenian stress makes direct reference to particular vowel qualities. In later work, Shih (2016Shih ( , 2018 and Shih & de Lacy (2020) make the stronger claim that even sonority cannot influence stress assignment. A similar claim is also made by Rasin (2017).…”
Section: Discussionmentioning
confidence: 98%
“…Goedemans & van Zanten 2007, Tabain, Fletcher & Butcher 2014. Similarly, while the book proposes constraints that 'relate sonority directly to … stress' (20), agreeing with de Lacy (2002,2004) and others, it has been demonstrated that many apparent sonority-driven stress cases have highly conflicting descriptions, and those descriptions do not match experimental results (Shih 2016(Shih , 2018aShih & de Lacy 2019).…”
mentioning
confidence: 89%